Konsep dan Pemahaman Filosifi Ilmu - Nikmarijal Nikmarijal (Tarbawy : Jurnal Pendidikan Islam, 2021)
Understanding the philosophy of science leads to a broad knowledge about the development of science-based on the references of early theories in the philosophy of science. James Ladyman in Understanding Philosophy of Science (2002) contains philosophical meanings starting from the discussion of scientific methods, problems of inductivism, realism and antirealism, explanations and inference, and the meaning of realism. The product of science and technology has a great influence on the process of running life and in shaping the environment. The importance of science is not only in its use in technology but science can be enjoyed (prestige) which is unmatched in society compared to an institution or agency. Most people tend to trust a scientist's word rather than a journalist, lawyer or political. True or false, science is often seen as the final form of an objective and rational research process and a scientist is considered an individual who is able to collect and interpret evidence and use it to arrive at a "scientifically proven" conclusion rather than just a belief or conjecture.